Influence of Thermal Plasma Energy on Phase Transitions of Nanodispersed Silicon Dioxide; Glass Physics and Chemistry; Vol. 48, iss. 5 - Shekhovtsov V. V. Valentin Valerievich (2022, 2022)
Title screen